2023
DOI: 10.1063/5.0134289
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on optoelectronic oscillators

Abstract: As a paradigmatic microwave photonic resonant system that is capable of producing high-quality self-sustained microwave oscillations, the optoelectronic oscillator (OEO) has been intensively investigated in recent years, and a diversity of new insights and breakthroughs have been proposed and demonstrated. In this perspective, we discuss the recent progress, opportunities, and challenges of OEOs. Specifically, an overview of different OEO schemes for single-frequency and complex microwave signal generation is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 148 publications
0
3
0
Order By: Relevance
“…(i) Comparison of the NEP under different frequencies with other detectors based on 2D materials, including graphene, [29,30,40,41] ZrGeSe, [36] PdSe 2 , [34] TaSe 2 , [32] PtTe 2 , [31] BP, [39,42,43] Ta 2 NiSe 5 , [44] and HgTe. [45] contrast, the response of device G is significantly stronger than that of the device A.…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…(i) Comparison of the NEP under different frequencies with other detectors based on 2D materials, including graphene, [29,30,40,41] ZrGeSe, [36] PdSe 2 , [34] TaSe 2 , [32] PtTe 2 , [31] BP, [39,42,43] Ta 2 NiSe 5 , [44] and HgTe. [45] contrast, the response of device G is significantly stronger than that of the device A.…”
Section: Resultsmentioning
confidence: 75%
“…(f) Comparison of the voltage responsivity of devices A-H. (g-h) Voltage noise spectra and NEP of device H at different gate voltages. (i) Comparison of the NEP under different frequencies with other detectors based on 2D materials, including graphene,[29,30,40,41] ZrGeSe,[36] PdSe 2 ,[34] TaSe 2 ,[32] PtTe 2 ,[31] BP,[39,42,43] Ta 2 NiSe 5 ,[44] and HgTe [45].…”
mentioning
confidence: 99%
“…Thermal-stimulated phase transition materials can be used in various smart devices, including signal processors, switches, and memory devices. [13][14][15][16][17][18][19] It is interesting to note that the physical properties of switchable dielectric materials change significantly when external stimuli are applied, including electric fields, temperature, and light. [20][21][22][23][24][25][26][27][28][29] Furthermore, it has been shown that a scientifically designed and tuned organic cation enables the material to have multiple properties, including ferroelectricity, pyroelectricity and piezoelectricity.…”
Section: Introductionmentioning
confidence: 99%